The Entrepreneurial University Engaging Publics, Intersecting Impacts - Taylor, Yvette; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
The entrepreneurial university has been tasked with making an impact. This collection presents professional-personal reflections on research experience and interpretative accounts of navigating fieldwork and broader publics, politics and practices of (dis)engagement primarily through a feminist, queer and gender studies lens.
Keywords: Science; Science; Science, general